The Occurrence of Apology Expressions in Moye’s Me Before You and After You: A Pragmatic Study - Albadri, Aliaa Ahmed (International Journal of Linguistics, 2022)
Pragmatics in general and speech acts theory in particular have witnessed an ever-lasting revolution in the number of studies, papers and articles that are conducted and written to deal with how their nature and state of affairs have been developing and to depict the extent which they have been reaching. The present study adds and completes, but not beautifies, other pragmatic portraits already demarcated by others. It is an in-depth treatment of apology expressions manipulated in Moye’s Me Before You and After You. It adopts a descriptive-analytical approach in which the frequencies and percentages are statistically used in the analysis of the apology expressions. The study concludes different findings as to how apology expressions of complex and simple types are concerned. The complex strategy of expressions is of more considerable variations than those of simple one in a way that for the complex one, the number of apology expressions is larger than the number of the other strategy.